New Records of Ground Beetles Genera (Coleoptera: Carabidae: Scaritinae: Clivinini) from Brazilian Caves - Letícia Aparecida de Oliveira; Daniela Hoyos-Benjumea; Tamires Zepon; Maria Elina Bichuette; Letícia Vieira (EntomoBrasilis, 2023)
The occurrence of the genera Aspidoglossa Putzeys, 1846, Paraclivina Kult, 1947, Oxydrepanus Putzeys, 1867, Pyramoides Bousquet, 2002, Semiardistomis Kult, 1950, Semiclivina Kult, 1947, Stratiotes Putzeys, 1846, and Whiteheadiana Perrault, 1994 is recorded for the first time for Brazilian caves. The specimens are deposited at the zoological collection of the Laboratório de Estudos Subterrâneos at Universidade Federal de São Carlos (LES) and are stored dipped in ethanol. A map and photographs of specimens of the genera are provided, as well as the specific records of their geographical distribution in caves.